Artificial faces are harder to remember. (November 2015) - Balas, Benjamin; Pacella, Jonathan
Highlights: We compared memory and discrimination for real and artificial faces. Artificial faces were identity-matched to real faces. Memory performance was poorer for artificial faces. Discrimination was also poorer, but this effect is smaller. Abstract: Observers interact with artificial faces in a range of different settings and in many cases must remember and identify computer-generated faces. In general, however, most adults have heavily biased experience favoring real faces over synthetic faces. It is well known that face recognition abilities are affected by experience such that faces belonging to "out-groups" defined by race or age are more poorly remembered and harder to discriminate from one another than faces belonging to the "in-group". Here, we examine the extent to which artificial faces form an "out-group" in this sense when other perceptual categories are matched. We rendered synthetic faces using photographs of real human faces and compared performance in a memory task and a discrimination task across real and artificial versions of the same faces. We found that real faces were easier to remember, but only slightly more discriminable than artificial faces. Artificial faces were also equally susceptible to the well-known face inversion effect, suggesting that while these patterns are still processed by the human visual system in a face-like manner, artificial appearance does compromise the efficiency of face processing.